ChemInform Abstract: Palladium‐Catalyzed anti‐Markovnikov Oxidation of Allylic Amides to Protected β‐Amino Aldehydes. Issue 23 (June 2015) - Dong, Jia Jia; Harvey, Emma C.; Fananas‐Mastral, Martin; Browne, Wesley R.; Feringa, Ben L.
Abstract The preparation of N‐protected β‐amino aldehydes is achieved with excellent selectivity for the anti‐Markovnikov aldehyde products and full retention of the configuration at the allylic carbon.